Respostas
respondido por:
1
- (- a) - ( + b) - ( - c) + ( - d)
= + a - b + c - d
******************************************************************
Regra de sinais:
menos ( - ) com menos ( - ) = mais (+)
menos ( - ) com mais ( + ) = menos ( - )
menos ( - ) com menos ( - ) = mais ( + )
mais ( + ) com menos ( - ) = menos ( - )
= + a - b + c - d
******************************************************************
Regra de sinais:
menos ( - ) com menos ( - ) = mais (+)
menos ( - ) com mais ( + ) = menos ( - )
menos ( - ) com menos ( - ) = mais ( + )
mais ( + ) com menos ( - ) = menos ( - )
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
(-) + (-) = (-)